Mesoparameter Calibration and Macro-Mesoparameter Correlation of Tailing Sand. (1st September 2022) - Du, Changbo; Liang, Lidong; Cheng, Hailong; Yi, Fu; Niu, Ben
Abstract : The aim of this study was to explore the correlation between mesoparameters (normal stiffness k n, tangential stiffness k s, and friction coefficient fric) and macromechanical parameters (cohesion, internal friction angle, and peak principal stress as well as its corresponding stress variables) of the particle flow code in 3-dimension (PFC3D) built-in linear contact model, which is suitable for simulating cohesionless materials that are similar to tailing sand. A triaxial test model was established using PFC3D, and nonspherical particles were developed by the clump command. Several numerical triaxial tests were performed under different confining pressures and mesoparameters. The results showed that the linear contact model is effective in simulating sandy soil, and the corresponding gradation of particles should be given. No one-to-one correspondence was found between the macromechanical parameters and the mesoparameters. Each macromechanical parameter was most affected by a certain mesoparameter, and the degree of influence was much greater than that of the other mesoparameters. The macro- and mesoparameters were strongly correlated. The stiffness ratio (k n / k s ) mainly affected the cohesion value, the friction coefficient of fillers (pebble-fric) mainly affected the internal friction angle and the peak principal stress, the normal stiffness (k n ) of particles mainly affected the strain corresponding to the peak principal stress, and the influence of the side wall friction coefficient (wall-fric) was not the strongest but was non-negligible. The microparameter calibration of the contact model can follow the order of parameter adjustment proposed in this study, which can facilitate and enhance the accuracy of the parameter calibration process of the linear contact model.